2011
DOI: 10.3109/02699206.2011.584136
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in idiom production in adulthood

Abstract: To investigate whether idiom production was vulnerable to age-related difficulties, we asked forty younger (ages 18-30) and forty older healthy adults (ages 60-85) to produce idiomatic expressions in a story-completion task. Younger adults produced significantly more correct idiom responses (73%) than older adults (60%) did. When older adults generated partially correct responses, they were less likely than younger participants to eventually produce the complete target idiom (Old: 32 % / Young: 70%); first-wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The participants had to provide their explanation by using a single word, a sentence, or a longer formulation. Age effects have been found in the production of idiomatic expressions with the result that younger adults (ages 18-30 years) have been found to produce significantly more correct idiom responses than older adults aged 60-85 (Conner et al, 2011). Moreover, the older adults in this study produce proportionately more partial responses than do the younger adults even when the target idioms was equally familiar.…”
Section: Theoretical Issues Addressed In the Processing Of Idiomatic mentioning
confidence: 60%
See 1 more Smart Citation
“…The participants had to provide their explanation by using a single word, a sentence, or a longer formulation. Age effects have been found in the production of idiomatic expressions with the result that younger adults (ages 18-30 years) have been found to produce significantly more correct idiom responses than older adults aged 60-85 (Conner et al, 2011). Moreover, the older adults in this study produce proportionately more partial responses than do the younger adults even when the target idioms was equally familiar.…”
Section: Theoretical Issues Addressed In the Processing Of Idiomatic mentioning
confidence: 60%
“…In psycholinguistics, a number of studies have attempted to investigate how idiomatic expressions are processed in different populations, such as healthy adults, patients (e.g., Hillert, 2004;Papagno & Caporali, 2007), or children (e.g., Caillies & Le Sourn-Bissaoui, 2008;Levorato, Nesi, & Cacciari, 2004), as well as in different tasks, such as comprehension (e.g., Caillies & Butcher, 2007;Caillies & Declercq, 2011) and production (e.g., Conner et al, 2011;Sprenger et al, 2006). The neural correlates of idiom processing have also been investigated (e.g., Hillert & Buracas, 2009).…”
mentioning
confidence: 99%
“…We know of no research comparing older and younger subjects on formulaic language proportions in spontaneous speech, as designed in this study. However, a related, recent study concerning age differences in healthy individuals suggested a mild reduction in idiom production tasks in older persons (Conner et al, 2011). In our study, however, no significant differences in proportion of formulaic expressions were seen between the early- and late-onset groups, who also differed significantly in age.…”
Section: Discussionmentioning
confidence: 99%
“…More intriguingly, figurative language skills, by taking longer to acquire, may manifest some vulnerability both in developmental deficits and across the life-span. Research in typical ageing suggests that older adults produce fewer idioms and may benefit more from cueing than younger speakers (Conner et al 2011), and findings from acquired deficits, such as aphasia, have shown impaired idiom comprehension (Cacciari et al 2006;Milburn et al 2018). Problems with figurative language have been systematically documented in developmental deficits, for example autism spectrum disorder (ASD) (Volden and Phillips 2010;Ramberg et al 1996).…”
Section: Introductionmentioning
confidence: 99%